Influence of genetic polymorphism and trauma on cortical structures and PTSD severity: Imaging genetics generalized structured component analysis - Jin, Min Jin; Cho, Gyeongcheol; Jeon, Hyeonjin; Choi, Younyoung; Hwang, Heungsun; Lee, Seung-Hwan (Frontiers in Psychiatry, 2025)
ObjectiveThe changes in brain structures affected by potentially traumatic events (PTEs) and polymorphisms of various genes are associated with posttraumatic stress disorder (PTSD). Our study investigated the pathophysiology of PTSD along with PTEs, genes, and brain regions of interest (ROIs) via imaging genetics generalized structured component analysis (IG-GSCA).MethodsA total of 231 participants (137 healthy volunteers and 94 PTSD patients) were enrolled. We performed T1-weighted structural magnetic resonance imaging, genotyping for nine genes (SLC6A4, FKBP5, ADCYAP1R1, BDNF, COMT, HTR3A, DRD2, NR3C1, and OXTR), and psychological assessments measuring PTEs, PTSD symptoms, and alcohol problems. Genes, PTEs, and their interactions were set as predictors for volumes of 60 brain ROIs, and volumes of the 60 ROIs were set as predictors for the PTSD severity, implying that volumes of brain ROIs were set to mediate the effects of genes and PTEs on the PTSD severity.ResultsOur results suggested that HTR3A was related to the volume of the anterior cingulate gyrus and NR3C1 was related to the volume of the central operculum. Also, volumes of the central operculum, occipital fusiform gyrus, and anterior cingulate gyrus were negatively associated with the severity of PTSD, while PTEs were positively associated with PTSD severity.ConclusionsThis study is one of the few that examined the relationships between various factors related to PTSD symptom severity, including genetics, environment, gene-environment interactions, and brain regions of interest (ROIs), all within a single model. The findings indicated mediating pathways from the HTR3A gene polymorphism to PTSD symptom severity through the volume of the anterior cingulate gyrus, and from the NR3C1 gene polymorphism to PTSD symptom severity via the volume of the central operculum. However, only the indirect effect involving NR3C1 was statistically significant. Additionally, the study found a significant association between the occipital fusiform gyrus and PTSD symptom severity.